Investigation of the dielectric Properties of (PPAB) terminated by phenylenediamine doped by Na2[Fe(CN)5.NO].2H2O using Lumped equivalent circuit (Baghdad Science Journal, 2016)
The aim of this paper is to demonstrate the effect of Na2[Fe(CN)5.NO].2H2O impurity (0.1 M) concentration on the dielectrical properties of poly (P-Aminobenzaldehyde) terminated by pheneylenediamine in the frequency and temperature ranges (1-100)KHz and (283-348) K respectively.These properties include dissipation factor, series and parallel resistance, series and parallel capacitance, real and imaginary part of the dielectric constant, a.c conductivity and impedance (real and imaginary) part, that have been deduced from equivalent circuit. The investigation shows that adding Na2[Fe(CN)5.NO].2H2O as additive to the polymer lead to increase of the dielectric constant with increasing temperature and it is decreasing with increasing the frequency .The dissipation factor is increasing with as the frequency increased.